Restoration of a forest ecosystem: The effects of vegetation and dispersal capabilities on the reassembly of plant-dwelling arthropods - Majer, Jonathan; Moir, M. L.; Brennan, K. E. C. (2005)
Restoration of degraded forest ecosystems is critical to conservation, but it is unknown if all components can be successfully restored. Despite the obvious dependence of plant-dwelling arthropods on plants, there are few empirical tests to show if restoring the plants also restores the plant-dwelling arthropods, or if other factors inhibit recolonisation. This paper tests the congruence in reassembly trajectory between these two groups and the role of dispersal capabilities on arthropod recolonisation, using Hemiptera. Plants and arthropods were sampled along a chronosequence of individual mine pits representing increasing ages since restoration works, and surrounding unmined forest. Changes in the richness, composition and structural complexity of the vegetation are described.